Meter Issues in Ruben Dario’s “Lo fatal”: scansion and stanza structure - Alcoholado Feltstrom, Antonio (Anales de Literatura Hispanoamericana, 2021)
This paper focuses on problematic meter practices in the poem “Lo fatal”, mainly scansion anomalies and enjambment examples that defy the Alexandrine verse design and the traditional relevance of line final stress, altogether with its unique stanza structure. It considers a delivery design of line number 8 based on observations of language facts in the study of both Spanish phonetics and meters, and suggests the scansion of line 12 according to inner rhythm in the poem and the use of enjambment in other lines of the same composition, while reviewing its possible sonnet stanza structure denomination.